Reforming the Monetary System: Should it be the Core Motivation of Sharia-compliant CBDC? - Hichem Hamza (Journal of Islamic Economics and Finance Studies, 2025)
Throughout the Islamic history of money, Fulūs (copper coins) and paper money emerged in Muslim societies as a monetary phenomenon, alongside with gold (Dinars) and silver (Dirhams) as sovereign Islamic currencies under Sharia terms. In recent years, this phenomenon has been extended to digital currencies, precisely central bank digital currency (CBDC), which raises questions about its role and functions in the monetary system. In the literature, the motivations of CBDC are essentially the financial system efficiency, the financial inclusion, and the confrontation of cryptocurrencies' widespread use; however, these motivations are secondary compared to the need for reforming the current monetary system. This paper aims to demonstrate that the core motivation of the CBDC should be the reform of the monetary system.  In this regard, this research examines the core and primary motivation of CBDC theoretically as a new currency, aiming to fulfill an effective economic and monetary role in accordance with a reformist Islamic perspective. Fundamentally, the core motivation of CBDC could be the opportunity to reform the monetary system in Muslim societies, which is deeply rooted in interest rates, money creation, and excessive indebtedness. This paper employs a descriptive-analytical methodology grounded in a normative approach to examine the challenges associated with the use of CBDC in promoting monetary sovereignty, stability, and fulfilling the functions of money in accordance with Sharia. The core motivation of CBDC is based on two main axes: the reinforcement of monetary sovereignty and the rethinking of the money functions in compliance with the principles of Sharia, allowing a strong connection of the financial sector with the real sector. This study concludes that the optimal Sharia- compliant CBDC is conditioned on being fully sovereign, legal, society-accepted, gold-backed, Zakāh-based, hoard-free, interest-free, investment-based, publicly available, fully reserve-based, and non-subject to maturity transformation.